Copolymers, molded bodies, injection molded bodies and coated electric wires
Patent Information
- Application Number
- CN202280016114.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-30
- Filing Date
- 2022-01-31
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-01-31
AI Technical Summary
[0015]根据本发明,能够提供一种共聚物,其能够通过注射成型法以高生产率得到表面平滑性优异的注射成型体,能够得到水蒸气低透过性非常优异、150℃耐磨耗性、氮低透过性、试剂低透过性、高温拉伸蠕变特性、对反复载荷的耐劣化性、高温时刚性和耐臭氧性优异、即使在高温下也不易变形、即使在与试剂接触的情况下也不易产生龟裂、氟离子不易溶出到双氧水等试剂中的成型体。
Smart Images

Figure BDA0004404569190000051 
Figure BDA0004404569190000191 
Figure BDA0004404569190000221
Abstract
Description
Technical Field
[0001] This invention relates to copolymers, molded articles, injection molded articles, and coated wires. Background Technology
[0002] Patent Document 1 describes a coated wire characterized in that it is formed by coating a core wire with a TFE-based copolymer, wherein the TFE-based copolymer has TFE units from tetrafluoroethylene [TFE] and PAVE units from perfluoro(alkyl vinyl ether) [PAVE], wherein the PAVE units account for more than 5% by mass and less than 20% by mass of all monomer units, and the unstable terminal groups are relative to each 1×10 6 The number of carbon atoms in each TFE copolymer is less than 10, and the melting point is above 260°C.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent Application Publication No. 2009-059690 Summary of the Invention
[0006] The problem that the invention aims to solve
[0007] The purpose of this invention is to provide a copolymer that can be injection molded with high productivity to obtain injection molded articles with excellent surface smoothness, and can produce articles with excellent low water vapor permeability, abrasion resistance at 150°C, low nitrogen permeability, low reagent permeability, high temperature tensile creep characteristics, resistance to degradation under repeated loads, excellent rigidity and ozone resistance at high temperatures, resistance to deformation even at high temperatures, resistance to cracking even when in contact with reagents, and low fluoride ion dissolution into reagents such as hydrogen peroxide.
[0008] Methods for solving problems
[0009] According to the present invention, a copolymer is provided comprising tetrafluoroethylene units and perfluoro(propyl vinyl ether) units, wherein the content of perfluoro(propyl vinyl ether) units is 3.3% to 4.2% by mass relative to all monomer units, the melt flow rate at 372°C is 27.0 g / 10 min to 35.0 g / 10 min, and the number of functional groups per 10 6 The main chain has fewer than 20 carbon atoms.
[0010] The copolymer of the present invention preferably has a melt flow rate of 27.0 g / 10 min to 33.0 g / 10 min at 372°C.
[0011] In addition, according to the present invention, an injection-molded article is provided which contains the above-mentioned copolymer.
[0012] In addition, according to the present invention, a coated wire is provided having a coating layer containing the above-mentioned copolymer.
[0013] In addition, according to the present invention, a molded body is provided, which is a molded body containing the above-mentioned copolymer, wherein the molded body is a wafer carrier, a gasket or a wire coating.
[0014] The effects of the invention
[0015] According to the present invention, a copolymer can be provided that can be obtained by injection molding with high productivity, resulting in injection molded articles with excellent surface smoothness, excellent water vapor permeability, abrasion resistance at 150°C, low nitrogen permeability, low reagent permeability, high temperature tensile creep characteristics, resistance to degradation under repeated loads, excellent rigidity and ozone resistance at high temperatures, resistance to deformation even at high temperatures, resistance to cracking even when in contact with reagents, and resistance to fluoride ion dissolution into reagents such as hydrogen peroxide. Detailed Implementation
[0016] The specific embodiments of the present invention will be described in detail below, but the present invention is not limited to the following embodiments.
[0017] The copolymer of the present invention contains tetrafluoroethylene (TFE) units and perfluoro(propyl vinyl ether) (PPVE) units.
[0018] Polymeric materials containing TFE and PPVE units (PFA) exhibit excellent chemical resistance and are therefore used as forming materials for wafer carriers used in handling, storage, cleaning, and drying wafers. In recent years, the use of larger diameter wafers and the need for larger wafer carriers to improve semiconductor manufacturing efficiency have led to increased demand. Furthermore, since wafer carriers are in direct contact with wafers, they require high cleanliness to prevent wafer contamination. Moreover, wafer carriers must possess high durability to withstand repeated cleaning with water or reagents and drying with heat. When using a rotary dryer to dry wafers housed within the wafer carrier, durability against centrifugal forces is also required.
[0019] Patent Document 1 describes a TFE-based copolymer having TFE units from tetrafluoroethylene [TFE] and PAVE units from perfluoro(alkyl vinyl ether) [PAVE], wherein the PAVE units exceed 5% by mass of all monomer units, thereby improving melt processability and crack resistance. However, copolymers that can provide molded articles with high cleanliness and high durability are not yet known.
[0020] Discovery: By appropriately adjusting the PPVE unit content, melt flow rate (MFR), and number of functional groups in copolymers containing TFE and PPVE units, the moldability of the copolymer is significantly improved, while exhibiting excellent low water vapor permeability. This results in molded bodies with excellent abrasion resistance at 150°C, low nitrogen permeability, low reagent permeability, high-temperature tensile creep characteristics, resistance to degradation under repeated loads, high-temperature rigidity and ozone resistance, resistance to deformation even at high temperatures, resistance to cracking even in contact with reagents, and low fluoride ion leaching into reagents such as hydrogen peroxide. Therefore, by using the copolymer of the present invention, large wafer carriers with excellent surface smoothness can be manufactured with high productivity. Furthermore, wafer carriers obtained using the copolymer of the present invention are less prone to wafer contamination, are less susceptible to damage even after repeated cleaning with water, ozone water, or reagents, and are less susceptible to damage even under heavy centrifugal force.
[0021] Furthermore, the copolymer of the present invention can be formed at high speed on small-diameter core wires without causing coating breakage by extrusion molding. Thus, the copolymer of the present invention can be used not only as a material for wafer carriers, but also for a wide range of applications such as wire coating.
[0022] The copolymers of the present invention are melt-processable fluoropolymers. Melt processability refers to the ability to melt and process the polymer using existing processing equipment such as extruders and injection molding machines.
[0023] The content of PPVE units in the copolymer is 3.3% to 4.2% by mass relative to all monomer units. The content of PPVE units in the copolymer is preferably 3.4% by mass or more, more preferably 3.5% by mass or more, even more preferably 3.6% by mass or more, particularly preferably 3.7% by mass or more, preferably 4.1% by mass or less, more preferably 4.0% by mass or less, and even more preferably 3.9% by mass or less. If the content of PPVE units in the copolymer is too high, it is prone to deformation at high temperatures, exhibiting low water vapor permeability, low nitrogen permeability, low reagent permeability, poor high-temperature tensile creep characteristics, and poor rigidity at high temperatures. If the content of PPVE units in the copolymer is too low, it is prone to cracking upon contact with reagents, or exhibits poor abrasion resistance at 150°C, poor resistance to degradation under repeated loads, and poor ozone resistance.
[0024] The content of TFE units in the copolymer is preferably 95.8% to 96.7% by mass relative to all monomer units, more preferably 95.9% by mass or more, even more preferably 96.0% by mass or more, more preferably 96.6% by mass or less, even more preferably 96.5% by mass or less, particularly preferably 96.4% by mass or less, and most preferably 96.3% by mass or less. If the content of TFE units in the copolymer is too low, it may be prone to deformation at high temperatures, or exhibit low water vapor permeability, low nitrogen permeability, low reagent permeability, poor high-temperature tensile creep characteristics, and poor rigidity at high temperatures. If the content of TFE units in the copolymer is too high, it may be prone to cracking upon contact with reagents, and its abrasion resistance at 150°C, resistance to degradation under repeated loads, and ozone resistance may deteriorate.
[0025] In this invention, the content of each monomer unit in the copolymer is determined by... 19 Determined by F-NMR method.
[0026] The copolymer may also contain monomer units from monomers capable of copolymerizing with TFE and FAVE. In this case, the content of monomer units capable of copolymerizing with TFE and PPVE is preferably 0 to 0.9% by mass, more preferably 0.05% to 0.6% by mass, and even more preferably 0.1% to 0.5% by mass, relative to all monomer units of the copolymer.
[0027] Monomers capable of copolymerizing with TFE and PPVE include hexafluoropropylene (HFP) and CZ. 1 Z 2 =CZ 3 (CF2) n Z 4 (where Z) 1 Z 2 and Z 3 Same or different, represented by H or F, Z 4 Vinyl monomers (represented by H, F, or Cl, where n represents an integer from 2 to 10), CF2 = CF-ORf 1 (where Rf) 1 Perfluoro(alkyl vinyl ether) [PAVE] (except for PPVE) represented by perfluoroalkyl groups having 1 to 8 carbon atoms, and CF2=CF-OCH2-Rf 1 (where Rf is in the formula) 1 This refers to perfluoroalkyl groups having 1 to 5 carbon atoms. Alkyl perfluorovinyl ether derivatives, etc., are also included. HFP is preferred.
[0028] The copolymer is preferably selected from at least one of the groups consisting of copolymers composed only of TFE units and PPVE units, and TFE / HFP / PPVE copolymers, and more preferably copolymers composed only of TFE units and PPVE units.
[0029] The melt flow rate (MFR) of the copolymer is 27.0 g / 10 min to 35.0 g / 10 min. The MFR of the copolymer is preferably 27.1 g / 10 min or more, more preferably 28.0 g / 10 min or more, even more preferably 29.0 g / 10 min or more, preferably 34.0 g / 10 min or less, more preferably 33.9 g / 10 min or less, even more preferably 33.3 g / 10 min or less, even more preferably 33.0 g / 10 min or less, particularly more preferably 32.9 g / 10 min or less, especially preferably 32.0 g / 10 min or less, very preferably 31.0 g / 10 min or less, and most preferably 30.0 g / 10 min or less. By ensuring the MFR of the copolymer is within the aforementioned range, the copolymer exhibits improved moldability and excellent low water vapor permeability. This results in molded bodies with excellent abrasion resistance at 150°C, low nitrogen permeability, low reagent permeability, high-temperature tensile creep characteristics, resistance to degradation under repeated loads, high-temperature rigidity and ozone resistance, resistance to deformation even at high temperatures, resistance to cracking even in contact with reagents, and low fluoride ion dissolution in reagents such as hydrogen peroxide. If the MFR is too low, it is difficult to obtain injection molded bodies with excellent surface smoothness when injecting the copolymer, or the resulting molded bodies may have poor low water vapor permeability, low nitrogen permeability, and high-temperature rigidity. If the MFR is too high, the resulting molded bodies may have poor abrasion resistance at 150°C and poor ozone resistance, or may easily crack when in contact with reagents.
[0030] In this invention, MFR is a value obtained according to ASTM D1238 using a melt index meter in the form of the mass (g / 10 min) of polymer flowing out of a nozzle with an inner diameter of 2.1 mm and a length of 8 mm every 10 minutes at 372°C and a load of 5 kg.
[0031] MFR can be adjusted by modifying the type and amount of polymerization initiator and the type and amount of chain transfer agent used in monomer polymerization.
[0032] In this invention, every 10 of the copolymer 6 The number of functional groups per main chain carbon atom is less than 20. For every 10... 6 The number of functional groups per carbon atom in the main chain is preferably 15 or less, more preferably 10 or less, and even more preferably less than 6. By keeping the number of functional groups in the copolymer within the above range, it is possible to obtain a molded body with excellent ozone resistance and that does not easily allow fluoride ions to dissolve into reagents such as hydrogen peroxide.
[0033] The identification of the types of functional groups and the determination of the number of functional groups mentioned above can be achieved using infrared spectroscopy.
[0034] Regarding the number of functional groups, specifically, it was determined using the following method. First, the above copolymer was cold-pressed to produce a film with a thickness of 0.25 mm to 0.3 mm. The film was analyzed by Fourier transform infrared spectroscopy to obtain the infrared absorption spectrum of the above copolymer, and a differential spectrum was obtained compared with the background spectrum of a fully fluorinated copolymer without functional groups. The number of functional groups in the above copolymer was calculated from the absorption peaks of specific functional groups shown in the differential spectrum according to the following formula (A). 6 The number of functional groups N per carbon atom.
[0035] N = I × K / t (A)
[0036] I: Absorbance
[0037] K: Correction coefficient
[0038] t: Membrane thickness (mm)
[0039] For reference, the absorption frequencies, molar absorptivity, and correction factors for some functional groups are shown in Table 1. Furthermore, the molar absorptivity was determined using FT-IR measurements of low-molecular-weight model compounds.
[0040] [Table 1]
[0041] Table 1
[0042]
[0043] The absorption frequencies of -CH2CF2H, -CH2COF, -CH2COOH, -CH2COOCH3, and -CH2CONH2 are tens of Kaiser (cm) lower than those of -CF2H, -COF, free -COOH, and bonded -COOH, -COOCH3, and -CONH2, respectively, as shown in the table. -1 ).
[0044] For example, the number of functional groups in -COF refers to the number of functional groups originating from the absorption frequency of -CF2COF, which is 1883 cm⁻¹. -1 The number of functional groups derived from the absorption peak at 1840 cm⁻¹ and the absorption frequency originating from -CH₂COF were also determined. -1 The total number of functional groups obtained from the absorption peak at the given location.
[0045] Functional groups are those present at the ends of the main chain or side chains of the copolymer, and those present in the main chain or side chains. The number of functional groups can be the total number of -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2, and -CH2OH.
[0046] The aforementioned functional groups are introduced into the copolymer, for example, through chain transfer agents or polymerization initiators used in the manufacturing of the copolymer. For instance, when an alcohol is used as a chain transfer agent, or when a peroxide having a -CH2OH structure is used as a polymerization initiator, -CH2OH is introduced to the ends of the copolymer's main chain. Alternatively, the aforementioned functional groups are introduced to the ends of the copolymer's side chains by polymerizing monomers containing functional groups.
[0047] By fluorinating the copolymer having such functional groups, copolymers having the number of functional groups within the aforementioned range can be obtained. That is, the copolymer of the present invention is preferably a fluorinated copolymer. The copolymer of the present invention also preferably has a -CF3 terminal group.
[0048] The melting point of the copolymer is preferably 295°C to 315°C, more preferably 300°C or higher, even more preferably 303°C or higher, particularly preferably 304°C or higher, most preferably 305°C or higher, and more preferably 310°C or lower. By keeping the melting point within the above range, a copolymer that provides superior sealing properties, especially at high temperatures, can be obtained.
[0049] In this invention, the melting point can be determined using a differential scanning calorimeter (DSC).
[0050] The water vapor permeability of the copolymer is preferably 8.0 g·cm / m. 2 The copolymer of the present invention exhibits excellent low water vapor permeability due to appropriate adjustments to the PPVE unit content, melt flow rate (MFR), and number of functional groups in copolymers containing TFE and PPVE units. Therefore, moisture is difficult to penetrate into the molded body formed from the copolymer, thus suppressing contamination of the wafer caused by the outflow of contaminants from the wafer carrier when the molded body is used as a wafer carrier.
[0051] In this invention, water vapor transmission rate can be measured at 95°C for 30 days. The specific measurement of water vapor transmission rate can be performed using the methods described in the examples.
[0052] The nitrogen permeability of the copolymer is preferably 240 cm⁻¹. 3 ·mm / (m 2 The copolymers of the present invention exhibit excellent low nitrogen permeability due to the appropriate adjustment of the PPVE unit content, melt flow rate (MFR), and number of functional groups in copolymers containing TFE and PPVE units.
[0053] In this invention, the nitrogen permeability coefficient can be measured under test conditions of 70°C and 0% RH. The specific measurement of the nitrogen permeability coefficient can be performed using the methods described in the examples.
[0054] The preferred methyl ethyl ketone (MEK) permeability of the copolymer is 58.0 mg·cm / m. 2 • days or less. The copolymers of the present invention exhibit excellent MEK low permeability due to appropriate adjustments to the PPVE unit content, melt flow rate (MFR), and number of functional groups in copolymers containing TFE and PPVE units. That is, by using the copolymers of the present invention, molded articles that are less susceptible to permeation by reagents such as MEK can be obtained.
[0055] In this invention, MEK transmittance can be measured at 60°C for 60 days. The specific measurement of MEK transmittance can be performed using the method described in the examples.
[0056] The storage modulus (E') of the copolymer at 150°C is preferably 115 MPa or more, more preferably 120 MPa or more, even more preferably 125 MPa or more, preferably 1000 MPa or less, more preferably 500 MPa or less, and even more preferably 300 MPa or less. By keeping the storage modulus (E') of the copolymer at 150°C within the above range, a copolymer that provides a molded article that is not easily deformed even at high temperatures can be obtained.
[0057] Storage modulus (E') can be determined by dynamic viscoelasticity measurement within the range of 30℃ to 250℃ at a heating rate of 2℃ / min and a frequency of 10Hz. The storage modulus (E') at 150℃ can be increased by adjusting the PPVE unit content and melt flow rate (MFR) of the copolymer.
[0058] The repulsive force of the copolymer at 150°C is preferably 0.55 MPa or more, more preferably 0.60 MPa or more, further preferably 0.65 MPa or more, even more preferably 0.70 MPa or more, particularly preferably 0.75 MPa or more, especially preferably 0.80 MPa or more, and most preferably 0.85 MPa or more. The upper limit is not particularly limited and can be 3.00 MPa or less. The repulsive force at 150°C can be increased by adjusting the PPVE unit content, melt flow rate (MFR), and number of functional groups in the copolymer. High repulsive force means that the molded body formed from the copolymer is not easily deformed even at high temperatures.
[0059] The repulsive force can be calculated as follows: After deforming the test piece obtained from the copolymer at a compression deformation rate of 50%, place it at 150°C for 18 hours, release the compression state, place it at room temperature for 30 minutes, and then measure the height of the test piece (the height of the test piece after compression deformation). The repulsive force can be calculated from the height of the test piece after compression deformation and the storage modulus (MPa) at 150°C using the following formula.
[0060] Repulsive force at 150℃ (MPa) = (t2 - t1) / t1 × E'
[0061] t1: Original height (mm) of the test piece before compression deformation × 50%
[0062] t2: Height of the test piece after compression deformation (mm)
[0063] E': Energy storage modulus at 150℃ (MPa)
[0064] The copolymers of the present invention can be manufactured by polymerization methods such as suspension polymerization, solution polymerization, emulsion polymerization, and bulk polymerization. Emulsion polymerization or suspension polymerization is preferred as the polymerization method. In these polymerizations, conditions such as temperature and pressure, polymerization initiators, and other additives can be appropriately set according to the composition and amount of the copolymer.
[0065] Oil-soluble or water-soluble free radical polymerization initiators can be used as polymerization initiators.
[0066] Oil-soluble free radical polymerization initiators can be well-known oil-soluble peroxides, and the following substances can be cited as representative examples:
[0067] Dialkyl percarbonate esters, such as di-n-propyl percarbonate, diisopropyl percarbonate, disec-butyl percarbonate, and di-2-ethoxyethyl percarbonate;
[0068] Peroxide esters such as tert-butyl peroxide isobutyrate and tert-butyl perpentyl peroxide;
[0069] Dialkyl peroxides such as di-tert-butyl peroxide;
[0070] Di[fluoro(or fluorochloro)acyl] peroxides; etc.
[0071] Examples of diacyl peroxides include those represented by [(RfCOO)-]2 (where Rf is a perfluoroalkyl, ω-hydroperfluoroalkyl, or fluorochloroalkyl).
[0072] Examples of di[fluoro(or fluorochloro)acyl]peroxides include, for example, di(ω-hydro-dodecanoyl)peroxide, di(ω-hydro-tetradecanoyl)fluoroheptanoyl)peroxide, di(ω-hydro-hexadecanoyl)fluorononanoyl)peroxide, di(perfluoropropionyl)peroxide, di(perfluorobutyryl)peroxide, di(perfluoropentanoyl)peroxide, di(perfluorohexanoyl)peroxide, di(perfluoroheptanoyl)peroxide, di(perfluorooctanoyl)peroxide, di(perfluorononanoyl)peroxide, di(ω-chloro-hexafluorobutyryl)peroxide, and di... (ω-chloro-decafluorohexanoyl) peroxide, di(ω-chloro-tetrafluorooctanoyl) peroxide, ω-hydro-dodecanoheptafluorononanoyl-peroxide, ω-chloro-hexafluorobutyryl-ω-chloro-decafluorohexanoyl-peroxide, ω-hydro-dodecanoheptafluorobutyryl-perfluorobutyryl-peroxide, di(dichloropentafluorobutyryl) peroxide, di(trichlorooctafluorohexanoyl) peroxide, di(tetrachloroundecanoyl) peroxide, di(pentachlorotetrafluorodecanoyl) peroxide, di(undecachlorotetrafluorotetradecanoyl) peroxide, di(undecachlorotetrafluorotetradecanoyl) peroxide, etc.
[0073] Water-soluble free radical polymerization initiators can be well-known water-soluble peroxides, such as ammonium, potassium, and sodium salts of persulfate, perboric acid, perchloric acid, superphosphoric acid, and percarbonate; organic peroxides such as disuccinate peroxide and diglutaric acid peroxide; tert-butyl maleate peroxide; and tert-butyl hydroperoxide. Reducing agents such as sulfites can also be used in combination with peroxides, with the amount used relative to the peroxide ranging from 0.1 to 20 times.
[0074] In polymerization, surfactants, chain transfer agents, and solvents can be used, each of which can be existing and well-known substances.
[0075] As the surfactant, known surfactants can be used, such as nonionic surfactants, anionic surfactants, and cationic surfactants. Among these, fluorinated anionic surfactants are preferred, and more preferably, fluorinated anionic surfactants with straight or branched chains having 4 to 20 carbon atoms, with or without ether-bonded oxygen (i.e., oxygen atoms can be inserted between carbon atoms). The amount of surfactant added (relative to the polymerization water) is preferably 50 ppm to 5000 ppm.
[0076] Examples of chain transfer agents include: hydrocarbons such as ethane, isopentane, n-hexane, and cyclohexane; aromatics such as toluene and xylene; ketones such as acetone; acetates such as ethyl acetate and butyl acetate; alcohols such as methanol and ethanol; thiols such as methyl mercaptan; and halogenated hydrocarbons such as carbon tetrachloride, chloroform, dichloromethane, and chloromethane. The amount of chain transfer agent added varies depending on the chain transfer constant of the compound used, and is typically used in the range of 0.01% to 20% by mass relative to the polymerization solvent.
[0077] Examples of solvents include water and mixed solvents of water and alcohol.
[0078] In suspension polymerization, fluorinated solvents can be used in addition to water. Examples of fluorinated solvents include hydrochlorofluorocarbons such as CH3CClF2, CH3CCl2F, CF3CF2CCl2H, and CF2ClCF2CFHCl; chlorofluorocarbons such as CF2ClCFClCF2CF3 and CF3CFClCFClCF3; hydrofluorocarbons such as CF3CFHCFHCF2CF2CF3, CF2HCF2CF2CF2CF2H, and CF3CF2CF2CF2CF2CF2CF2H; and CH3OC2F5. Hydrofluoroethers such as CH3OC3F5CF3CF2CH2OCHF2, CF3CHFCF2OCH3, CHF2CF2OCH2F, (CF3)2CHCF2OCH3, CF3CF2CH2OCH2CHF2, and CF3CHFCF2OCH2CF3; perfluorocyclobutanes such as CF3CF2CF2CF3, CF3CF2CF2CF2CF3, and CF3CF2CF2CF2CF2CF3, with perfluoroalkanes being preferred. From the perspectives of suspension and economy, the amount of fluorinated solvent relative to the aqueous medium is preferably 10% to 100% by mass.
[0079] There is no particular limitation on the polymerization temperature, which can be 0 to 100°C. The polymerization pressure is appropriately determined according to the type, amount, vapor pressure, polymerization temperature, and other polymerization conditions used, and is usually 0 to 9.8 MPaG.
[0080] When an aqueous dispersion containing a copolymer is obtained through polymerization, the copolymer can be recovered by precipitating it, washing, and drying. Alternatively, when a copolymer is obtained as a slurry through polymerization, the copolymer can be recovered by removing the slurry from the reaction vessel, washing, and drying. The copolymer can also be recovered as a powder by drying.
[0081] The copolymer obtained through polymerization can also be granulated. There are no particular limitations on the granulation method; existing known methods can be used. For example, methods such as using a single-screw extruder, twin-screw extruder, or tandem extruder to melt-extrude the copolymer and cut it to a specified length to form granules can be employed. The extrusion temperature during melt extrusion needs to be varied depending on the melt viscosity of the copolymer and the manufacturing method; preferably, it is between the copolymer's melting point +20°C and the copolymer's melting point +140°C. There are no particular limitations on the copolymer cutting method; existing known methods such as wire cutting, thermal cutting, underwater cutting, and sheet cutting can be used. The volatile components in the granules can also be removed by heating (degassing treatment). Alternatively, the granules can be treated by contacting them with warm water at 30°C to 200°C, steam at 100°C to 200°C, or hot air at 40°C to 200°C.
[0082] The copolymer obtained by polymerization can also be fluorinated. Fluorination can be carried out by contacting the unfluorinated copolymer with a fluorinated compound. Through fluorination, thermally unstable functional groups such as -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, and -CONH2, as well as relatively thermally stable functional groups such as -CF2H, can be converted into extremely thermally stable -CF3. As a result, the total number of functional groups (-COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, -CONH2, and -CF2H) of the copolymer can be easily adjusted to the above-mentioned range.
[0083] There are no particular limitations on fluorine-containing compounds; examples of fluorine radical sources that generate fluorine radicals under fluorination conditions can be cited. Examples of such fluorine radical sources include F2 gas, CoF3, AgF2, UF6, OF2, N2F2, CF3OF, and fluorinated halogens (e.g., IF5, ClF3).
[0084] Fluorine radical sources such as F2 gas can be 100% concentrated, but from a safety perspective, it is preferable to mix them with an inert gas and dilute them to 5% to 50% by mass before use, and more preferably to 15% to 30% by mass. Examples of such inert gases include nitrogen, helium, and argon; from an economic perspective, nitrogen is preferred.
[0085] The conditions for fluorination are not particularly limited; the molten copolymer can be brought into contact with a fluorinated compound. However, it is generally carried out at a temperature below the melting point of the copolymer, preferably between 20°C and 240°C, and more preferably between 100°C and 220°C. The fluorination treatment is typically carried out for 1 hour to 30 hours, preferably 5 hours to 25 hours. Fluorination is preferably carried out by bringing the unfluorinated copolymer into contact with fluorine gas (F2 gas).
[0086] The copolymers of the present invention can also be mixed with other components as needed to obtain compositions. Examples of other components include fillers, plasticizers, processing aids, mold release agents, pigments, flame retardants, lubricants, light stabilizers, weather stabilizers, conductive agents, antistatic agents, ultraviolet absorbers, antioxidants, foaming agents, fragrances, oils, softeners, defluorinated hydrogen agents, etc.
[0087] Examples of fillers include silica, kaolin, clay, organoclay, talc, mica, alumina, calcium carbonate, calcium terephthalate, titanium dioxide, calcium phosphate, calcium fluoride, lithium fluoride, cross-linked polystyrene, potassium titanate, carbon, boron nitride, carbon nanotubes, and glass fiber. Examples of conductive agents include carbon black. Examples of plasticizers include dioctyl phthalate and pentaerythritol. Examples of processing aids include carnauba wax, sulfone compounds, low molecular weight polyethylene, and fluorinated additives. Examples of defluorinating agents include organonium and amidines.
[0088] Other polymers besides the copolymers described above can also be used as other components. Examples of other polymers include fluoropolymers, fluororubbers, and non-fluorinated polymers, in addition to the copolymers described above.
[0089] Examples of methods for manufacturing the above composition include: dry mixing of the copolymer with other components; pre-mixing of the copolymer with other components using a mixer, followed by melt mixing using a kneader, melt extruder, etc.; etc.
[0090] The copolymers of the present invention or the above-described compositions can be used as processing aids, molding materials, etc., and are preferably used as molding materials. Aqueous dispersions, solutions, suspensions, and copolymer / solvent systems of the copolymers of the present invention can also be used as coatings, or for encapsulation, impregnation, and film casting. However, due to the aforementioned properties, the copolymers of the present invention are preferably used as the above-described molding materials.
[0091] The copolymer of the present invention or the above composition can also be molded to obtain a molded body.
[0092] The method for molding the above-mentioned copolymer or composition is not particularly limited, and examples include injection molding, extrusion molding, compression molding, blow molding, transfer molding, rotational molding, and roll forming. Among these molding methods, extrusion molding, compression molding, injection molding, or transfer molding are preferred, and injection molding, extrusion molding, or transfer molding are more preferred because they can produce molded articles with high productivity. In other words, as the molded article, an extruded molded article, a compression molded article, an injection molded article, or a transfer molded article is preferred, and injection molded articles, extrusion molded articles, or transfer molded articles are more preferred because they can be produced with high productivity. Injection molded articles are even more preferred. By using injection molding to mold the copolymer of the present invention, injection molded articles with excellent surface smoothness can be obtained with high productivity.
[0093] The molded body containing the copolymer of the present invention can be, for example, a nut, bolt, joint, membrane, bottle, gasket, wire sheath, tube, hose, pipe, valve, sheet, seal, gasket, can, roller, container, stopcock, connector, filter housing, filter cover, flow meter, pump, wafer carrier, wafer box, etc.
[0094] The copolymers, compositions, or molded articles of the present invention can be used for, for example, the following purposes.
[0095] Food packaging films, lining materials for fluid transport pipelines used in food manufacturing processes, gaskets, sealing materials, thin sheets, and other fluid transport components for food manufacturing equipment;
[0096] Chemical stoppers, packaging films, lining materials for fluid delivery pipelines used in chemical manufacturing processes, gaskets, sealing materials, thin plates, and other reagent delivery components;
[0097] Inner lining components for reagent containers and piping in chemical equipment and semiconductor plants;
[0098] O-rings / pipes / gaskets, valve core materials, hoses, sealing materials, etc. used in the fuel system and peripheral devices of automobiles; hoses, sealing materials, and other fuel delivery components used in the AT system of automobiles.
[0099] The carburetor flange gaskets, shaft seals, valve stem seals, sealing materials, hoses, etc. used in the engine and peripheral devices of automobiles; brake hoses, air conditioning hoses, radiator hoses, wire sheathing materials, and other automobile components.
[0100] O-rings, tubes, gaskets, valve core materials, hoses, sealing materials, rollers, washers, diaphragms, connectors and other reagent delivery components for semiconductor manufacturing equipment;
[0101] Coating and ink components for coating equipment, such as coating rollers, hoses, tubes, and ink containers;
[0102] Food and beverage conduits, hoses, belts, gaskets, connectors and other food and beverage conveying components, food packaging materials, and glass cooking equipment;
[0103] Pipes, hoses, and other components used for waste liquid transportation;
[0104] Pipes, hoses, and other components used for high-temperature liquid transfer;
[0105] Pipes, hoses and other components used in steam piping;
[0106] Corrosion-resistant tape for piping, such as tape wrapped around the deck of a ship;
[0107] Various coating materials, such as wire coating materials, optical fiber coating materials, transparent surface coating materials and backing agents applied to the light incident side of photovoltaic elements in solar cells;
[0108] The diaphragm and various sliding components such as gaskets in a diaphragm pump;
[0109] Weather-resistant covers for agricultural films, various roofing materials, and sidewalls;
[0110] Interior materials used in the construction industry, and glass-like covering materials such as non-combustible fire-resistant safety glass;
[0111] Lining materials such as laminated steel sheets used in the home appliance industry.
[0112] Further examples of fuel delivery components used in the fuel systems of the aforementioned automobiles include fuel hoses, filler hoses, and evaporator hoses. These fuel delivery components can also be used for fuels resistant to acidic gasoline, alcohol-based fuels, and fuels containing gasoline additives such as those resistant to methyl tert-butyl ether and amines.
[0113] The stoppers and packaging films used for the aforementioned chemicals exhibit excellent resistance to acids and other chemicals. Additionally, anti-corrosion tape wrapped around the piping of chemical equipment can also be cited as a component for transporting the aforementioned reagents.
[0114] Examples of such molded bodies include radiator water chambers for automobiles, reagent tanks, bellows, partitions, rollers, gasoline tanks, waste liquid conveying containers, high-temperature liquid conveying containers, and fish farming and aquaculture tanks.
[0115] Further examples of the molded bodies mentioned above include components used in automobile bumpers, door panels, dashboards, food processing devices, cooking machines, waterproof and oil-proof glass, lighting-related instruments, indicator panels and housings of OA instruments, electrically illuminated signboards, displays, LCD screens, mobile phones, printer chassis, electrical and electronic components, groceries, trash cans, bathtubs, prefabricated bathrooms, exhaust fans, lighting frames, etc.
[0116] The molded articles containing the copolymer of the present invention have excellent low water vapor permeability, low nitrogen permeability, low reagent permeability, high temperature tensile creep characteristics, resistance to degradation under repeated loads, high temperature rigidity and ozone resistance. They are not easily deformed even at high temperatures, and are not easily cracked even when in contact with reagents. They are also less likely to cause fluoride ions to dissolve into reagents such as hydrogen peroxide. Therefore, they are suitable for use in nuts, bolts, joints, gaskets, valves, stopcocks, connectors, filter housings, filter covers, flow meters, pumps, etc.
[0117] The molded articles containing the copolymer of the present invention have excellent low water vapor permeability, low abrasion resistance at 150°C, low nitrogen permeability, low reagent permeability, high temperature tensile creep characteristics, resistance to degradation under repeated loads, high temperature rigidity and ozone resistance. They are not easily deformed even at high temperatures, and are not easily cracked even when in contact with reagents. They are also less likely to cause fluoride ions to dissolve into reagents such as hydrogen peroxide. Therefore, they are suitable for use as gaskets, sealing gaskets and other compressed components.
[0118] Even when deformed at a high compression rate, the compressed member of the present invention exhibits high repulsive force. The compressed member of the present invention can be used in a state of compression deformation at a compression rate of 10% or more, and can be used in a state of compression deformation at a compression rate of 20% or more, or 25% or more. By using the compressed member of the present invention to deform at such a high compression rate, a certain degree of resilience can be maintained over a long period, and sealing and insulation properties can be maintained over a long period.
[0119] Even when deformed at high temperatures with a high compression rate, the compressed component of the present invention exhibits high storage modulus, high resilience, and high repulsive force. The compressed component of the present invention can be used in a state of compression deformation at 150°C or higher with a compression rate of 10% or higher, and can be used in a state of compression deformation at 150°C or higher with a compression rate of 20% or higher or 25% or higher. By using the compressed component of the present invention to deform at such high temperatures with a high compression rate, it can maintain a certain degree of resilience even at high temperatures for a long period, and can maintain its sealing and insulation properties at high temperatures for a long time.
[0120] Regarding the aforementioned compressive deformation rate, when the compressed member is used in a compressed state, it is the compressive deformation rate of the part with the largest compressive deformation rate. For example, when a flat compressed member is used in a state where it is compressed along its thickness direction, it is the compressive deformation rate in the thickness direction. Furthermore, for example, when the compressed member is used in a state where only a portion of it is compressed, it is the compressive deformation rate of the part with the largest compressive deformation rate among the compressed portions.
[0121] The size and shape of the compressed member of the present invention can be appropriately set according to the application and are not particularly limited. The shape of the compressed member of the present invention can be, for example, ring-shaped. In addition, the compressed member of the present invention can have a circular, elliptical, or quadrilateral shape with rounded corners when viewed from above, and has a through hole in its central part.
[0122] The compressed component of the present invention is preferably used as a component for constructing a non-aqueous electrolyte battery. The compressed component of the present invention exhibits excellent low water vapor permeability, excellent abrasion resistance at 150°C, low nitrogen permeability, low reagent permeability, excellent high-temperature tensile creep characteristics, excellent resistance to degradation under repeated loading, excellent rigidity and ozone resistance at high temperatures, and excellent sealing performance at high temperatures. Therefore, it is particularly suitable as a component for use in contact with the non-aqueous electrolyte in a non-aqueous electrolyte battery. That is, the compressed component of the present invention can have a liquid-contacting surface for contacting the non-aqueous electrolyte in a non-aqueous electrolyte battery.
[0123] The compressed component of the present invention does not easily allow water vapor to pass through. Therefore, by using the compressed component of the present invention, it is possible to suppress water vapor from passing through the secondary battery from the outside. As a result, by using the compressed component of the present invention, it is possible to suppress the degradation of battery performance and the shortening of battery life in non-aqueous electrolyte batteries.
[0124] Because it can further suppress the degradation of battery performance and shorten the battery life of non-aqueous electrolyte batteries, the water vapor permeability of the compressed component of the present invention is preferably 8.8 g·cm / m. 2 The following, and more preferably, is 8.4 g·cm / m 2 The following, and more preferably, is 8.0 g·cm / m 2 The water vapor permeability of the compressed component can be measured at 95°C for 30 days.
[0125] As for non-aqueous electrolyte batteries, there are no particular limitations as long as the battery contains a non-aqueous electrolyte; examples include lithium-ion secondary batteries and lithium-ion capacitors. Furthermore, components constituting non-aqueous electrolyte batteries include sealing components and insulating components.
[0126] The non-aqueous electrolyte is not particularly limited and can be one or more of the following known solvents: propylene carbonate, ethylene carbonate, butyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate. The non-aqueous electrolyte battery may further include an electrolyte. The electrolyte is not particularly limited and can be LiClO4, LiAsF6, LiPF6, LiBF4, LiCl, LiBr, CH3SO3Li, CF3SO3Li, cesium carbonate, etc.
[0127] The compressed component of the present invention can preferably be used as a sealing component such as a sealing gasket or sealing pad, or as an insulating component such as an insulating gasket or insulating sealing pad. A sealing component is used to prevent leakage of liquid or gas or intrusion of liquid or gas from the outside. An insulating component is used for electrical insulation. The compressed component of the present invention can also be used for both sealing and insulation purposes.
[0128] Even when deformed at high temperatures with a high compression rate, the compressed component of the present invention exhibits high storage modulus, high recovery amount, and high repulsive force, thus enabling suitable use in high-temperature environments. For example, the compressed component of the present invention is preferably used in environments with a maximum temperature of 40°C or higher. For example, the compressed component of the present invention is preferably used in environments with a maximum temperature of 150°C or higher. Examples of situations where the compressed component of the present invention can reach such high temperatures include, for example, the case where other battery components are installed in the battery by welding after the compressed component is installed in a compressed state; the case where a non-aqueous electrolyte battery generates heat; etc.
[0129] The compressible member of the present invention exhibits excellent low water vapor permeability. Even when deformed at high temperatures with a high compression ratio, it displays high storage modulus, high recovery, and high repulsion, making it suitable for use as a sealing member or insulating member for non-aqueous electrolyte batteries. For example, during charging of batteries such as non-aqueous electrolyte secondary batteries, the battery temperature may temporarily exceed 40°C, and particularly exceed 150°C. The compressible member of the present invention, when used in batteries such as non-aqueous electrolyte secondary batteries, deforms at high temperatures with a high compression ratio, and thus does not compromise its high resilience even when in contact with a non-aqueous electrolyte at high temperatures. Therefore, when the compressible member of the present invention is used as a sealing member, it exhibits excellent sealing properties, which are maintained for extended periods even at high temperatures. Furthermore, the compressible member of the present invention, containing the aforementioned copolymer, possesses excellent insulating properties. Therefore, when the compressible member of the present invention is used as an insulating member, it provides a strong seal with two or more conductive members, preventing short circuits for extended periods.
[0130] By using extrusion molding to form the copolymer of the present invention, even with a small core diameter, the coating will not break. A thin coating layer can be formed on a small-diameter core at a high traction speed, and a coating layer with excellent electrical properties can be formed. Therefore, it is suitable as a material for forming wire coatings. Thus, wires with a coating layer containing the copolymer of the present invention exhibit almost no defects such as sparking, even with a small core diameter and a thin coating layer, and also possess excellent electrical properties.
[0131] The coated wire has a core wire and a coating layer disposed around the core wire containing the copolymer of the present invention. For example, an extruded body formed by melt-extruding the copolymer of the present invention onto the core wire can be used as the coating layer. The coated wire is suitable for LAN cables (Eathernet cables), high-frequency transmission cables, flat cables, heat-resistant cables, etc., and is particularly suitable for transmission cables such as LAN cables (Eathernet cables) and high-frequency transmission cables.
[0132] For example, copper, aluminum, or other metallic conductors can be used as the core wire material. The core wire diameter is preferably 0.02 mm to 3 mm. More preferably, the core wire diameter is 0.04 mm or more, even more preferably 0.05 mm or more, and particularly preferably 0.1 mm or more. Even more preferably, the core wire diameter is 2 mm or less.
[0133] Specific examples of core wires include AWG (American wire gauge)-46 (solid copper wire with a diameter of 40μm), AWG-26 (solid copper wire with a diameter of 404μm), AWG-24 (solid copper wire with a diameter of 510μm), and AWG-22 (solid copper wire with a diameter of 635μm).
[0134] The thickness of the coating layer is preferably 0.1 mm to 3.0 mm. The thickness of the coating layer is also preferably less than 2.0 mm.
[0135] Coaxial cables are an example of high-frequency transmission cables. Coaxial cables typically have a structure consisting of an inner conductor, an insulating sheath, an outer conductor layer, and a protective sheath layer layered sequentially from the core to the outer periphery. Molded bodies containing the copolymer of the present invention can be suitable as the insulating sheath layer containing the copolymer. The thickness of each layer in the above structure is not particularly limited; typically, the diameter of the inner conductor is about 0.1 mm to 3 mm, the thickness of the insulating sheath is about 0.3 mm to 3 mm, the thickness of the outer conductor layer is about 0.5 mm to 10 mm, and the thickness of the protective sheath is about 0.5 mm to 2 mm.
[0136] The coating may contain air bubbles, which are preferably evenly distributed in the coating.
[0137] The average bubble diameter is not limited, but is preferably 60 μm or less, more preferably 45 μm or less, further preferably 35 μm or less, even more preferably 30 μm or less, particularly preferably 25 μm or less, and especially preferably 23 μm or less. Furthermore, the average bubble diameter is preferably 0.1 μm or more, more preferably 1 μm or more. The average bubble diameter can be obtained by acquiring an electron microscope image of the wire cross-section, calculating the diameter of each bubble using image processing, and then averaging the results.
[0138] The foaming rate of the coating layer can be 20% or more. More preferably, it is 30% or more, further preferably 33% or more, and even more preferably 35% or more. There is no particular upper limit, for example, 80%. The upper limit of the foaming rate can also be 60%. The foaming rate is calculated as ((specific gravity of wire coating material - specific gravity of coating layer) / specific gravity of wire coating material) × 100. The foaming rate can be adjusted appropriately according to the application, for example, by adjusting the gas insertion amount in the extruder described later, or by selecting the type of dissolved gas.
[0139] The coated wire may also have other layers between the core wire and the coating layer, and may further have other layers (outer layers) around the coating layer. If the coating layer contains air bubbles, the wire of the present invention may also be a two-layer structure (skin-foam body) with a non-foamed layer inserted between the core wire and the coating layer; a two-layer structure (foam body-skin body) with a non-foamed layer coated on the outer layer; and a three-layer structure (skin-foam body-skin body) with a non-foamed layer coated on the outer layer of the skin-foam body. The non-foamed layer is not particularly limited and may be a resin layer composed of TFE / HFP copolymers, TFE / PAVE copolymers, TFE / ethylene copolymers, vinylidene fluoride polymers, polyolefin resins such as polyethylene [PE], and resins such as polyvinyl chloride [PVC].
[0140] Coated wires can be manufactured, for example, by heating a copolymer using an extruder and extruding it onto the core wire while the copolymer is in a molten state to form a coating.
[0141] During the formation of the coating layer, the copolymer can also be heated, and gas can be introduced into the copolymer while it is in a molten state to form the aforementioned coating layer containing bubbles. The gas can be, for example, dichlorofluoromethane, nitrogen, carbon dioxide, or a mixture of these gases. The gas can be introduced into the heated copolymer in the form of pressurized gas, or it can be generated by mixing a chemical foaming agent into the copolymer. The gas dissolves in the molten copolymer.
[0142] In addition, the copolymers of the present invention are suitable for use as materials in products for high-frequency signal transmission.
[0143] As for the aforementioned high-frequency signal transmission products, there are no particular limitations as long as the product is used for high-frequency signal transmission. Examples include (1) insulating boards for high-frequency circuits, insulating materials for connecting components, printed wiring boards, and other molded boards; (2) bases for high-frequency vacuum tubes, radomes, and other molded bodies; and (3) sheathed wires such as coaxial cables and LAN cables. The aforementioned high-frequency signal transmission products are suitable for use in satellite communication equipment, mobile phone base stations, and other equipment that utilizes microwaves, especially microwaves from 3 GHz to 30 GHz.
[0144] In the aforementioned high-frequency signal transmission products, the copolymer of the present invention, from the perspective of low dielectric loss tangent, is suitable for use as an insulator.
[0145] As for the molded plate described in (1) above, a printed wiring substrate is preferred from the perspective of obtaining good electrical characteristics. There are no particular limitations on the printed wiring substrate described above; examples include printed wiring substrates for electronic circuits in mobile phones, various computers, and communication devices. As for the molded body described in (2) above, an antenna radome is preferred from the perspective of low dielectric loss.
[0146] By molding the copolymers of the present invention using injection molding, sheets with excellent surface smoothness can be obtained with high productivity. Furthermore, the molded articles containing the copolymers of the present invention exhibit excellent low water vapor permeability, low abrasion resistance at 150°C, low nitrogen permeability, low reagent permeability, high-temperature tensile creep characteristics, resistance to degradation under repeated loads, high-temperature rigidity, and ozone resistance. They are not easily deformed even at high temperatures, are not prone to cracking even in contact with reagents, and do not easily leach fluoride ions into reagents such as hydrogen peroxide. Therefore, the molded articles containing the copolymers of the present invention are suitable for use as films or sheets.
[0147] The film of the present invention is useful as a release film. The release film can be manufactured by molding the copolymer of the present invention through melt extrusion molding, calendering, compression molding, casting, etc. From the perspective of obtaining a uniform film, the release film can be manufactured by melt extrusion molding.
[0148] The membrane of this invention can be applied to the surface of rollers used in OA equipment. Furthermore, the copolymer of this invention can be molded into necessary shapes, such as sheets, films, or tubes, through extrusion molding, compression molding, or pressing, for use as a surface material for OA equipment rollers or belts. In particular, thin-walled tubes and membranes can be manufactured using melt extrusion molding.
[0149] The molded articles containing the copolymers of this invention exhibit excellent low water vapor permeability, low nitrogen permeability, low reagent permeability, high-temperature tensile creep characteristics, resistance to degradation under repeated loads, high-temperature rigidity, and ozone resistance. They are not easily deformed even at high temperatures, and are not prone to cracking even in contact with reagents. They also do not easily allow fluoride ions to leach into reagents such as hydrogen peroxide, making them suitable for use as bottles or tubes. The bottles or tubes of this invention allow for easy visual inspection of the contents and are less prone to damage during use.
[0150] The copolymer of the present invention can be injection molded into injection molded articles with high productivity. Furthermore, the resulting molded articles exhibit excellent surface smoothness, excellent low water vapor permeability, and excellent abrasion resistance at 150°C, low nitrogen permeability, low reagent permeability, high-temperature tensile creep characteristics, resistance to degradation under repeated loads, high-temperature rigidity, and ozone resistance. They are not easily deformed even at high temperatures, are not prone to cracking even when in contact with reagents, and do not easily leach fluoride ions into reagents such as hydrogen peroxide. Therefore, they are suitable for use in valves. Thus, valves containing the copolymer of the present invention can be manufactured with high productivity and are not easily damaged even with frequent opening and closing. They exhibit excellent low reagent permeability, high-temperature sealing, and low water vapor permeability. In the valve of the present invention, at least the liquid-contacting portion can be composed of the above-described copolymer. Additionally, the valve of the present invention can be a valve having a shell containing the above-described copolymer.
[0151] The embodiments have been described above, but it is understood that various changes can be made to the methods and details without departing from the spirit and scope of the claims.
[0152] Example
[0153] Next, embodiments will be given to illustrate the implementation of the present invention, but the present invention is not limited to the embodiments described.
[0154] The values in the examples were measured using the following methods.
[0155] (Monomer content)
[0156] The content of each monomer unit was determined by an NMR analyzer (e.g., an AVANCE300 high-temperature probe manufactured by Bruker BioSpin).
[0157] (Mel flow rate (MFR))
[0158] According to ASTM D1238, the mass (g / 10 min) of polymer flowing out of a nozzle with an inner diameter of 2.1 mm and a length of 8 mm per 10 minutes was determined using a melt indexer G-01 (manufactured by Toyo Seiki Co., Ltd.) at 372°C and a load of 5 kg.
[0159] (Number of functional groups)
[0160] The copolymer granules were cold-pressed to produce films with a thickness of 0.25 mm to 0.3 mm. The films were then scanned 40 times using a Fourier transform infrared spectroscopy (FT-IR) device (Spectrum One, PerkinElmer) to obtain infrared absorption spectra. A differential spectrum was obtained between this spectrum and the background spectrum of the fully fluorinated film, which lacks functional groups. The concentration of the sample relative to each 1 × 10⁻⁶ functional group was calculated from the absorption peaks of specific functional groups observed in the differential spectrum according to the following formula (A). 6 The number of functional groups N per carbon atom.
[0161] N = I × K / t (A)
[0162] I: Absorbance
[0163] K: Correction coefficient
[0164] t: Membrane thickness (mm)
[0165] For reference, the absorption frequencies, molar absorptivity, and correction factors for the functional groups in this invention are shown in Table 2. The molar absorptivity was determined by FT-IR measurements of the low-molecular-weight model compounds.
[0166] [Table 2]
[0167] Table 2
[0168]
[0169] (Melting point)
[0170] The first heating was performed using a differential scanning calorimeter (trade name: X-DSC7000, manufactured by Hitachi High-Tech Science) at a heating rate of 10°C / min, from 200°C to 350°C. Then, the temperature was cooled from 350°C to 200°C at a cooling rate of 10°C / min. The second heating was performed again at a heating rate of 10°C / min, from 200°C to 350°C. The melting point was determined from the peak value of the melting curve generated during the second heating process.
[0171] Example 1
[0172] 33.4 L of pure water was added to a 174 L autoclave, and after thorough nitrogen purging, 33.4 kg of perfluorocyclobutane, 0.83 kg of perfluoropropyl vinyl ether (PPVE), and 2.26 kg of methanol were added. The system temperature was maintained at 35 °C, and the stirring speed was maintained at 200 rpm. Next, tetrafluoroethylene (TFE) was injected to 0.6 MPa, followed by 0.066 kg of a 50% methanol solution of di-n-propyl dicarbonate, to initiate polymerization. As the pressure in the system decreased during polymerization, TFE was continuously supplied to maintain a constant pressure. For every 1 kg of TFE supplied, 0.042 kg of PPVE was added, and polymerization continued for 20.3 hours. After releasing the TFE and restoring the autoclave to atmospheric pressure, the resulting reaction product was washed with water and dried to obtain 33 kg of powder.
[0173] The obtained powder was melt-extruded at 360°C using a screw extruder (trade name: PCM46, manufactured by Ikebe Co., Ltd.) to obtain TFE / PPVE copolymer granules. The PPVE content of the obtained granules was determined using the method described above. The results are shown in Table 3.
[0174] The obtained granules were placed in a VVD-30 vacuum vibratory reactor (manufactured by Okawahara Seisakusho Co., Ltd.) and heated to 210°C. After evacuation, F2 gas diluted to 20% by volume with N2 gas was introduced to atmospheric pressure. 0.5 hours after the introduction of F2 gas, a temporary vacuum was applied, and F2 gas was introduced again. Then, after another 0.5 hours, a vacuum was applied again, and F2 gas was introduced again. This process of introducing F2 gas and evacuating the vacuum was repeated once every hour, and the reaction was carried out at 210°C for 10 hours. After the reaction was completed, the reactor was completely replaced with N2 gas to end the fluorination reaction. Various physical properties of the fluorinated granules were measured using the above method. The results are shown in Table 3.
[0175] Example 2
[0176] The PPVE was changed to 0.80 kg, the methanol to 2.42 kg, the PPVE was changed to an additional 0.041 kg for every 1 kg of TFE supplied, and the polymerization time was changed to 19.3 hours. Otherwise, fluorinated pellets were obtained in the same manner as in Example 1. The results are shown in Table 3.
[0177] Example 3
[0178] 34.0 L of pure water was added to a 174 L autoclave, and after thorough nitrogen purging, 30.4 kg of perfluorocyclobutane, 0.71 kg of perfluoropropyl vinyl ether (PPVE), and 2.05 kg of methanol were added. The system temperature was maintained at 35 °C, and the stirring speed was maintained at 200 rpm. Next, tetrafluoroethylene (TFE) was injected to 0.6 MPa, followed by 0.060 kg of a 50% methanol solution of di-n-propyl dicarbonate, to initiate polymerization. As the pressure in the system decreased during polymerization, TFE was continuously supplied to maintain a constant pressure. For every 1 kg of TFE supplied, 0.040 kg of PPVE was added, and polymerization continued for 18.5 hours. After releasing the TFE and restoring the autoclave to atmospheric pressure, the resulting reaction product was washed with water and dried to obtain 30 g of powder.
[0179] The obtained powder was melt-extruded at 360°C using a screw extruder (trade name: PCM46, manufactured by Ikebe Co., Ltd.) to obtain TFE / PPVE copolymer granules. The PPVE content of the obtained granules was determined using the method described above. The results are shown in Table 3.
[0180] The obtained granules were placed in a VVD-30 vacuum vibratory reactor (manufactured by Okawahara Seisakusho Co., Ltd.) and heated to 210°C. After evacuation, F2 gas diluted to 20% by volume with N2 gas was introduced to atmospheric pressure. 0.5 hours after the introduction of F2 gas, a temporary vacuum was applied, and F2 gas was introduced again. Then, after another 0.5 hours, a vacuum was applied again, and F2 gas was introduced again. This process of introducing F2 gas and evacuating the vacuum was repeated once every hour, and the reaction was carried out at 210°C for 10 hours. After the reaction was completed, the reactor was completely replaced with N2 gas to end the fluorination reaction. Various physical properties of the fluorinated granules were measured using the above method. The results are shown in Table 3.
[0181] Example 4
[0182] The PPVE was changed to 0.68 kg, the methanol to 1.85 kg, and the PPVE was increased by 0.038 kg for every 1 kg of TFE supplied. The polymerization time was changed to 18 hours. Otherwise, fluorinated pellets were obtained in the same manner as in Example 3. The results are shown in Table 3.
[0183] Example 5
[0184] The PPVE was changed to 0.66 kg, the methanol to 1.80 kg, and the PPVE was increased by 0.037 kg for every 1 kg of TFE supplied. The polymerization time was changed to 18 hours. Otherwise, fluorinated pellets were obtained in the same manner as in Example 3. The results are shown in Table 3.
[0185] Example 6
[0186] The PPVE was changed to 0.63 kg, the methanol to 1.90 kg, and the PPVE was increased by 0.036 kg for every 1 kg of TFE supplied. The polymerization time was changed to 18 hours. Otherwise, fluorinated pellets were obtained in the same manner as in Example 3. The results are shown in Table 3.
[0187] Comparative Example 1
[0188] 51.8 L of pure water was added to a 174 L autoclave, and after thorough nitrogen purging, 40.9 kg of perfluorocyclobutane, 1.79 kg of perfluoropropyl vinyl ether (PPVE), and 6.61 kg of methanol were added. The system temperature was maintained at 35 °C, and the stirring speed was maintained at 200 rpm. Next, tetrafluoroethylene (TFE) was injected to 0.64 MPa, followed by the addition of 0.051 kg of a 50% methanol solution of di-n-propyl peroxide dicarbonate, to initiate polymerization. Since the pressure within the system decreased as polymerization progressed, TFE was continuously supplied to maintain a constant pressure, with an additional 0.042 kg of PPVE added for every 1 kg of TFE supplied. Polymerization was terminated when the additional TFE amount reached 40.9 kg. Unreacted TFE was released, and the autoclave pressure was restored to atmospheric pressure. The resulting reaction product was then washed with water and dried to obtain 41.0 kg of powder.
[0189] The obtained powder was subjected to a fluorination reaction in the same manner as in Example 1 to obtain fluorinated granules. The results are shown in Table 3.
[0190] Comparative Example 2
[0191] The PPVE was changed to 0.73 kg, the methanol to 3.49 kg, and the PPVE was changed to an additional 0.040 kg for every 1 kg of TFE supplied. The polymerization time was changed to 20 hours. Otherwise, fluorinated pellets were obtained in the same manner as in Example 3. The results are shown in Table 3.
[0192] Comparative Example 3
[0193] The amount of pure water was changed to 26.6 L, PPVE to 0.77 kg, methanol to 5.10 kg, TFE was injected to 0.58 MPa, the 50% methanol solution of di-n-propyl peroxide was changed to 0.011 kg, PPVE was changed to an additional 0.031 kg for every 1 kg of TFE supplied, and the polymerization time was changed to 11 hours, yielding 15 kg of dried powder. Otherwise, fluorinated granules were obtained in the same manner as in Example 3. The results are shown in Table 3.
[0194] Comparative Example 4
[0195] The pure water was changed to 26.6 L, PPVE to 1.40 kg, methanol to 3.00 kg, TFE was added to a pressure of 0.57 MPa, the 50% methanol solution of di-n-propyl peroxide was changed to 0.014 kg, PPVE was changed to an additional 0.048 kg for every 1 kg of TFE supplied, and the polymerization time was changed to 21 hours. Otherwise, fluorinated granules were obtained in the same manner as in Example 3. The results are shown in Table 3.
[0196] Comparative Example 5
[0197] The PPVE was changed to 0.86 kg, the methanol to 1.50 kg, the PPVE was changed to an additional 0.046 kg for every 1 kg of TFE supplied, the polymerization time was changed to 21 hours, the heating temperature of the vacuum vibratory reactor was changed to 160°C, and the reaction was changed to be carried out at 160°C for 5 hours. Otherwise, fluorinated granules were obtained in the same manner as in Example 3. The results are shown in Table 3.
[0198] [Table 3]
[0199] Table 3
[0200]
[0201] The “<6” in Table 3 refers to a number of functional groups that is less than 6.
[0202] Next, the obtained granules were used to evaluate the following properties. The results are shown in Table 4.
[0203] (Reagent impregnation crack test)
[0204] With approximately 50g of the aforementioned granules placed in a mold (120mm inner diameter, 38mm height), the mixture was heated at 360°C for 20 minutes using a hot plate press, followed by water cooling under pressure of 1MPa to produce a molded body with a thickness of approximately 2mm. A rectangular dumbbell measuring 13.5mm × 38mm was used to punch the resulting sheet, yielding three test pieces. A 19mm × 0.45mm notched notch was made at the center of the long side of each test piece, according to ASTM D1693. The three notched test pieces and 25g of a 40% (w / w) aqueous solution of tetrabutylammonium hydroxide were placed in a 100mL polypropylene bottle. The bottle was heated at 100°C for 20 hours, after which the notched test pieces were removed. The three notched test pieces were then mounted in a stress cracking test fixture according to ASTM D1693, and the notches and their surrounding area were visually observed to count the number of cracks.
[0205] ○: The number of cracks is 0
[0206] ×: The number of cracks is more than 1.
[0207] (Water vapor transmission rate)
[0208] Using granulation and a thermoforming machine, sheet-like test pieces with a thickness of approximately 0.2 mm were produced. These were then placed in a test cup (with a transparency area of 12.56 cm²). 2 Place 18g of water inside a container, cover it with a sheet-like test piece, and secure it tightly with a PTFE gasket. Allow the sheet-like test piece to remain in contact with the water. After maintaining this temperature at 95℃ for 30 days, remove it and allow it to stand at room temperature for 2 hours to measure the mass loss. Measure the water vapor transmission rate (g·cm / m) using the following formula. 2 ).
[0209] Water vapor transmission rate (g·cm / m) 2 = Mass reduction (g) × Thickness of sheet test piece (cm) / Transmitting area (m²) 2 )
[0210] (Storage Modulus (E'))
[0211] The dynamic viscoelasticity was determined using a DVA-220 (manufactured by IT Measurement & Control Co., Ltd.). A thermoformed sheet with a length of 25 mm, a width of 5 mm, and a thickness of 0.2 mm was used as the sample test piece. The measurement was conducted within the range of 30℃ to 250℃ at a heating rate of 2℃ / min and a frequency of 10Hz, with the storage modulus (MPa) read at 150℃.
[0212] (Recovery Amount)
[0213] The recovery amount was determined according to the methods described in ASTM D395 or JIS K6262:2013.
[0214] Approximately 2g of the aforementioned granules were placed in a mold (inner diameter 13mm, height 38mm). The mixture was melted at 370°C for 30 minutes using a hot plate press, and then water-cooled while being pressurized at 0.2MPa (resin pressure) to produce a molded body with a height of approximately 8mm. The resulting molded body was then cut to produce a test piece with an outer diameter of 13mm and a height of 6mm. Using a compression device, the test piece was compressed at room temperature to a compression set of 50% (i.e., compressing the 6mm high test piece to a height of 3mm). The compressed test piece was then placed in an electric furnace, fixed to the compression device, and kept at 150°C for 18 hours. The compression device was removed from the furnace, and after cooling to room temperature, the test piece was removed. The recovered test piece was left at room temperature for 30 minutes, and its height was measured. The recovery amount was calculated using the following formula.
[0215] Recovery amount (mm) = t2 - t1
[0216] t1: Height of the spacer (mm)
[0217] t2: Height of the test piece removed from the compression device (mm)
[0218] In the above experiment, t1 = 3 mm.
[0219] (Repulsive force at 150℃)
[0220] Based on the results of the compression set test at 150℃ and the storage modulus measurement at 150℃, the repulsive force at 150℃ is calculated using the following formula.
[0221] Repulsive force at 150℃ (MPa) = (t2 - t1) / t1 × E'
[0222] t1: Height of the spacer (mm)
[0223] t2: Height of the test piece removed from the compression device (mm)
[0224] E': Energy storage modulus at 150℃ (MPa)
[0225] The molded body with high repulsive force at 150℃ is not easily deformed even at high temperatures, and has excellent sealing performance at high temperatures.
[0226] (Injection molding)
[0227] The copolymer was injection molded using an injection molding machine (Sumitomo Heavy Industries, Ltd., SE50EV-A) with a barrel temperature of 390°C, a mold temperature of 170°C, and an injection speed of 50 mm / s. A Cr-plated mold (100 mm × 100 mm × 2.5 mm) was used as the mold. The surface of the injection-molded body was visually inspected, and the surface smoothness was evaluated according to the following criteria.
[0228] 2: The surface was smooth and not rough.
[0229] 1: Roughness is observed only on the surface of the portion of the mold near the gate.
[0230] 0: Roughness is observed on most of the surface.
[0231] (Conditions for wire coating)
[0232] use A wire coating molding machine (manufactured by Tanabe Plastics Machinery Co., Ltd.) extrudes a coating copolymer onto a copper conductor with a conductor diameter of 0.50 mm to obtain a coated wire at the following coating thickness. The wire coating extrusion molding conditions are as follows.
[0233] a) Core conductor: Conductor diameter 0.50mm
[0234] b) Coating thickness: 0.15mm
[0235] c) Coated electric wire diameter: 0.80 mm
[0236] d) Electric wire drawing speed: 150 m / min
[0237] e) Extrusion conditions:
[0238] · Single-screw extrusion molding machine with barrel shaft diameter = 30 mm and L / D = 22
[0239] · Die (inner diameter) / sheet (outer diameter) = 8.0 mm / 5.0 mm
[0240] Set temperatures of the extruder: barrel section C-1 (330°C), barrel section C-2 (360°C), barrel section C-3 (375°C), head H (390°C), die head D-1 (405°C), die head D-2 (395°C). The core wire preheating was set to 80°C.
[0241] (Spark)
[0242] A spark tester (DENSOK HIGH FREQ SPARK TESTER) was installed inline on the coated electric wire, and the presence or absence of defects in the electric wire coating was evaluated at a voltage of 1500 V. Continuous molding was performed for 1 hour. A case with zero sparks was rated as acceptable (○), and a case where sparks were detected was rated as unacceptable (×).
[0243] (Coating breakage)
[0244] Electric wire coating molding was carried out continuously. A case where coating breakage occurred 1 or more times within 1 hour was regarded as non-continuously moldable (×), and a case where no coating breakage occurred was regarded as continuously moldable (○).
[0245] (Abrasion test)
[0246] Using pellets and a hot press molding machine, a sheet-shaped test piece with a thickness of about 0.2 mm was produced, from which a 10 cm × 10 cm test piece was cut out. The produced test piece was fixed on the test table of a Taber abrasion tester (No. 101 special type Taber abrasion tester, manufactured by Yasuda Seiki Seisakusho Co., Ltd.), and an abrasion test was performed using the Taber abrasion tester under the conditions of a test piece surface temperature of 150°C, a load of 500 g, an abrasion wheel CS-10 (ground 20 revolutions with #240 abrasive paper), and a rotation speed of 60 rpm. The weight of the test piece after 1000 revolutions was measured, and the weight of the test piece was further measured after a 5000-revolution test using the same test piece. The abrasion loss was determined by the following formula.
[0247] Abrasion loss (mg) = M1 - M2
[0248] M1: Weight of the test piece after 1000 revolutions (mg)
[0249] M2: Weight of the test piece (mg) after 5000 revolutions.
[0250] (Nitrogen permeability coefficient)
[0251] A sheet-like test piece with a thickness of approximately 0.1 mm was prepared using granulation and a hot press molding machine. Using the obtained test piece, nitrogen permeability was measured using a differential pressure gas permeability meter (L100-5000 type gas permeability meter, manufactured by Systech Illinois) according to the method described in JIS K7126-1:2006. The permeability area was found to be 50.24 cm². 2 The nitrogen transmittance value was obtained at a test temperature of 70℃ and a test humidity of 0%RH. Using the obtained nitrogen transmittance and the thickness of the test piece, the nitrogen transmittance coefficient was calculated using the following formula.
[0252] Nitrogen permeability (cm) 3 ·mm / (m 2 ·24h·atm))=GTR×d
[0253] GTR: Nitrogen Transmission Rate (cm) 3 / (m 2 ·24h·atm))
[0254] d: Thickness of the test piece (mm)
[0255] (Methanal ethyl ketone (MEK) permeability)
[0256] Using granulation and a thermoforming machine, sheet-like test pieces with a thickness of approximately 0.1 mm were produced. These were then placed in a test cup (with a transparency area of 12.56 cm²). 2 Place 10g of MEK inside a container, cover it with a sheet test piece, and secure it tightly with a PTFE gasket. Ensure the sheet test piece is in contact with the MEK. After maintaining this temperature at 60℃ for 60 days, remove the container and allow it to stand at room temperature for 1 hour to measure the mass loss. Calculate the MEK transmittance (mg·cm / m²) using the following formula. 2 ·sky).
[0257] MEK transmittance (mg·cm / m) 2 • Days) = [Mass reduction (mg) × Thickness of the test piece (cm)] / [Transmitting area (m²)] 2 )·Number of days (days)]
[0258] (Deflection under load at 95℃)
[0259] Using granulation and a hot press molding machine, sheet-like test pieces with a thickness of approximately 3 mm were prepared. 80 × 10 mm test pieces were cut from these pieces and heated in an electric furnace at 100°C for 20 hours. In addition to using the obtained test pieces, tests were conducted according to the method described in JIS K-K7191-1 using a heat distortion tester (manufactured by Yasuda Seiki Co., Ltd.) under the conditions of a test temperature of 30°C to 150°C, a heating rate of 120°C / hour, a bending stress of 1.8 MPa, and the flatwise method. The load deflection was calculated using the following formula. Sheets with low load deflection at 95°C exhibit excellent high-temperature rigidity.
[0260] Load-induced deflection (%) = a2 / a1 × 100
[0261] a1: Thickness of the test piece before the test (mm)
[0262] a2: Deflection at 95℃ (mm)
[0263] (Tensile creep test)
[0264] Tensile creep strain was determined using a Hitachi High-Tech TMA-7100. Sheets approximately 0.1 mm thick were prepared using a granulator and thermoforming machine. Samples 2 mm wide and 22 mm long were then fabricated from these sheets. The samples were mounted in the measuring fixture with a 10 mm gap between the clamps. A cross-sectional load of 3.32 N / mm² was applied to the samples. 2 The sample was subjected to a load and placed at 200°C. The displacement (mm) of the sample length was measured from 90 minutes to 1320 minutes after the start of the test. The ratio of the displacement (mm) to the initial sample length (10mm) was calculated (tensile creep strain (%)). Samples with low tensile creep strain (%) measured at 200°C for 1320 minutes do not easily elongate even under prolonged tensile loads in high-temperature environments, exhibiting excellent long-term tensile creep characteristics.
[0265] (60,000 tensile strength retention rate)
[0266] The tensile strength retention rate after 60,000 cycles was determined using a Shimadzu MMT-250NV-10 fatigue testing machine. A pellet approximately 2.4 mm thick was prepared using a granulator and thermoforming machine. A dumbbell-shaped sample (2.4 mm thickness, 5.0 mm width, and 22 mm measuring section length) was fabricated using ASTM D1708 micro-dumbbells. The sample was mounted in the testing fixture, which was then placed in a 150°C constant temperature bath with the sample mounted. Uniaxial tension was repeatedly applied with a stroke of 0.2 mm and a frequency of 100 Hz, and the tensile strength at each stroke (tensile strength at a stroke of +0.2 mm) was measured. The tensile strength retention rate after 60,000 cycles was calculated from the measured values using the following formula.
[0267] Tensile strength retention rate after 60,000 cycles (%) = Tensile strength (60,000 cycles) (mN) / Tensile strength (5,000 cycles) (mN) × 100
[0268] The tensile strength retention rate at 60,000 cycles is the ratio of the tensile strength after 60,000 repeated loads to the tensile strength after 5,000 repeated loads. Sheets with a high tensile strength retention rate at 60,000 cycles maintain their initial tensile strength even after 60,000 loads, demonstrating excellent resistance to degradation under repeated loads.
[0269] (Hydrogen peroxide immersion test)
[0270] 25g of granules were immersed in 50g of a 3% (w / w) hydrogen peroxide solution, heated in an electric furnace at 90°C for 20 hours, and then sterilized in a sterilizer at 121°C for 1 hour, before cooling to room temperature. The granules were removed from the aqueous solution, and TISAB solution (10) (manufactured by Kanto Chemical Co., Ltd.) was added to the remaining aqueous solution. The concentration of fluoride ions in the resulting aqueous solution was measured using a fluoride ion meter. The concentration of fluoride ions per unit weight of granules (amount of fluoride ions dissolved) was calculated from the measured values using the following formula.
[0271] Dissolved fluoride ion content (ppm by mass) = Measured value (ppm by mass) × Aqueous solution volume (g) / Granule weight (g)
[0272] (Ozone Exposure Test)
[0273] The copolymer was compressed at 350°C and 0.5 MPa to produce a 1 mm thick sheet, from which 10 × 20 mm samples were cut as specimens for ozone exposure testing. Ozone gas (ozone / oxygen = 10 / 90 volume%) generated by an ozone generator (trade name: SGX-A11MN (modified), manufactured by Sumitomo Seiki Kogyo Co., Ltd.) was connected to a PFA container filled with ion-exchanged water. Water vapor was added to the ozone gas while bubbling in the ion-exchanged water, and the gas was passed through the PFA tank containing the specimen at 0.7 L / min at room temperature, exposing the specimen to the moist ozone gas. After 30 days from the start of exposure, the specimen was removed, and the surface was gently rinsed with ion-exchanged water. The area from 5 μm to 200 μm depth to the specimen surface was observed using a transmission optical microscope at 100x magnification, and photographed along with a standard scale. Measurements were taken at 1 mm depth per 1 mm of the specimen surface. 2 The number of cracks with a length of 10 μm or more is evaluated according to the following criteria.
[0274] ○: The number of cracks is less than 10
[0275] ×: More than 10 cracks
[0276] (Dielectric loss tangent)
[0277] The granules were melt-molded to produce cylindrical test pieces with a diameter of 2 mm. These test pieces were then placed on a 6 GHz cavity resonator manufactured by Kanto Electronics Application Development Co., Ltd., and measurements were taken using a network analyzer manufactured by Agilent Technologies. The measurement results were analyzed using the analysis software "CPMA" manufactured by Kanto Electronics Application Development Co., Ltd. on a personal computer connected to the network analyzer, thereby determining the dielectric loss tangent (tanδ) at 20°C and 6 GHz.
[0278]
Claims
1. A copolymer comprising tetrafluoroethylene units and perfluoro(propyl vinyl ether) units, The content of perfluoro(propyl vinyl ether) units is 3.3% to 4.2% by mass relative to all monomer units. The content of tetrafluoroethylene units relative to all monomer units is 95.8%–96.7% by mass. The melt flow rate at 372℃ is 27.0 g / 10 min to 35.0 g / 10 min. The number of functional groups -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2, and -CH2OH relative to 10 6 The main chain has fewer than 20 carbon atoms.
2. The copolymer of claim 1, wherein, The content of perfluoro(propyl vinyl ether) units is 3.5% to 4.2% by mass relative to all monomer units, and the content of tetrafluoroethylene units is 95.8% to 96.5% by mass relative to all monomer units.
3. The copolymer as described in claim 1 or 2, wherein, The melt flow rate at 372℃ is 27.0 g / 10 min to 33.3 g / 10 min.
4. The copolymer as described in claim 1 or 2, wherein, The melt flow rate at 372℃ is 28.0 g / 10 min to 31.0 g / 10 min.
5. An injection-molded article comprising the copolymer according to any one of claims 1 to 4.
6. A coated wire having a coating layer comprising the copolymer of any one of claims 1 to 4.
7. A molded article comprising the copolymer according to any one of claims 1 to 4, wherein, The molded body is a wafer carrier, a gasket, or a wire coating.
Citation Information
Patent Citations
Covered electric wire, and coaxial cable
JP2009059690A
Modified fluorine-containing copolymer, fluorine resin molded article, and method for manufacturing fluorine resin molded article
CN104411752A
Fluoropolymers, fluoropolymer compositions and fluoropolymer dispersions
CN111727227A